X-3z=-19

Simple and best practice solution for X-3z=-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-3z=-19 equation:



X-3X=-19
We move all terms to the left:
X-3X-(-19)=0
We add all the numbers together, and all the variables
-2X+19=0
We move all terms containing X to the left, all other terms to the right
-2X=-19
X=-19/-2
X=9+1/2

See similar equations:

| 4*(x+4)=18*(x-3) | | 3x-12=5x+15 | | 13x=04 | | -2x-14=-3(x+4) | | 4(c+3)=13 | | 15=5y−78 | | 15=5(y−78) | | 43-x=0 | | 6(7x-4)=270 | | -18+53=-5(x+6) | | 9w-163=52 | | -2(2+5x)=16 | | 4f+23=8 | | 9(2x+1)=2x-7x | | 40x-16=4x | | 3(x+3)-4-2x/2=0.5 | | 8p^2+16p-71=-7 | | -7(2+7x)=-259 | | X+y=14;-X+3y=26 | | X=390-3/2y | | X+y=14-X+3y=26 | | -8x+1+6x=-3x=6 | | 8b=24b= | | 11=0.5t | | 2x2−10x+5=0 | | 4(-7x+3)=348 | | 7/8h-5/8=21 | | 3(4x+8)=-30+18 | | 3.5x=64=7884864 | | -4(6+3x)=-120 | | -3/4(-1x+9)=26 | | 3(−3x−3)−4x+3=3 |

Equations solver categories